Penyusunan rencana kontinjensi epidemi penyakit menular disebabkan oleh virus di Kota Banda Aceh [Development of contingency plan for infectious disease epidemics caused by viruses in Banda Aceh City] - Nasution, Abdillah Imron; Kurniawan, Hendra (Buletin Pengabdian, 2024)
Contingency Plan for Outbreak/Epidemic Disaster in Banda Aceh City is a document that contains the process of identifying and preparing future plans based on potential disaster conditions. The purpose of making a Contingency Plan document that becomes a reference in the disaster outbreak/epidemic of Infectious Diseases Caused by Viruses in the City of Banda Aceh. Method The preparation process involved all disaster management institutions and actors, both government and non-government. The scope of activities carried out are: Technical Team Meeting, Public Seminar, and Plan Finalization. The results obtained by the issuance of the Banda Aceh Mayor's Regulation for the Contingency Plan for the epidemic of infectious diseases caused by viruses in the city of Banda Aceh which is regulated in a Banda Aceh Mayor's Regulation No. 68 of 2021 concerning the Contingency Plan for the Epidemic of Infectious Diseases Caused by Viruses in the City of Banda Aceh. In conclusion, Banda Aceh City has realized preparedness for the threat of epidemics of diseases caused by viruses by involving multi-sectors. To improve the function and sustainability of the document, data updates and projections of resource needs are needed to support the implementation/activation of the contingency plan that has been prepared.